THE INTERRACIAL RELATIONSHIPS AMONG WOMEN IN THE HELP BY KATHRYN STOCKETT - Cindy Zahra Devita (Jurnal Sastra - Studi Ilmiah Sastra, 2024)
This journal analyzes the complexities and challenges of interracial relationships among women in Kathryn Stockett's "The Help," offering profound insights into the intricate dynamics of societal norms and racial dynamics in 1960s America. The novel intricately portrays the dynamics of friendships, alliances, and conflicts that arise between black maids and their white employers, illuminating the complex intersections of race, class, and gender. Through these relationships, the narrative highlights the potential for empathy, understanding, and solidarity across racial lines, challenging the barriers imposed by segregation and discrimination. Despite the resilience displayed by the characters, the novel underscores the enduring effects of racial injustice. Through its exploration of themes such as identity, empathy, and resilience in "The Help", this journal offers a nuanced portrayal of the human experience amidst the backdrop of racial tensions and also show support among women with racial differences. The result of this analysis aims to demonstrate that skin color and social class do not impede solidarity among women. Skeeter, a white woman, endeavors to protect and advocate for black maids, asserting that they are all equals and should not face discrimination.